Using wheat straw in beef cow rations - Peverley, B.; Corah, L.; McKee, M.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station, 2011)
We conducted two trials to study using wheat straw in rations of either lactating or gestating beef cows maintained in dry lot. In trial 1, cow weight changes the last 60 days of lactation were: alfalfa hay, +26.88 lbs; two-thirds alfalfa hay-one third chopped wheat straw, +27.94 lbs; one-third alfalfa hay and two thirds chopped wheat straw, -26.84 pounds. Gains by the cows’ calves; 146, 143, and 144 pounds, respectively did not differ statistically. Cows receiving one-third alfalfa hay and two-thirds chopped wheat straw lost condition as measured by weight/height ratios, while those on the other two treatments gained condition. The results suggest that beef cows in dry lot can perform satisfactorily on two-thirds alfalfa hay and one-third wheat straw.
Keywords: Beef; Wheat straw